2014
DOI: 10.1016/j.jaci.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Stress and asthma: Novel insights on genetic, epigenetic, and immunologic mechanisms

Abstract: In the United States, the economically disadvantaged and some ethnic minorities are often exposed to chronic psychosocial stressors and disproportionately affected by asthma. Current evidence suggests a causal association between chronic psychosocial stress and asthma or asthma morbidity. Recent findings suggest potential mechanisms underlying this association, including changes in the methylation and expression of genes that regulate behavioral, autonomic, neuroendocrine, and immunologic responses to stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
94
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 68 publications
(75 reference statements)
4
94
0
2
Order By: Relevance
“…This finding strongly supports an expanding body of literature linking stress-related disorders, such as PTSD, to the pathogenesis of asthma (14,21), and suggests that physicians treating adults with PTSD should be aware of their potentially increased risk of asthma. Whether treatment of PTSD prevents or helps treat asthma is unknown, but merits examination in future studies.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This finding strongly supports an expanding body of literature linking stress-related disorders, such as PTSD, to the pathogenesis of asthma (14,21), and suggests that physicians treating adults with PTSD should be aware of their potentially increased risk of asthma. Whether treatment of PTSD prevents or helps treat asthma is unknown, but merits examination in future studies.…”
Section: Discussionsupporting
confidence: 77%
“…Hyperventilation, often present in individuals with anxiety, could cause cooling and osmotic change in the bronchial epithelium, leading to increased airway responsiveness. Alternatively, PTSD may cause dysregulation of the hypothalamic pituitary axis and the sympathetic-adrenal-medullary system, ultimately leading to abnormal immune responses and increased airway inflammation (14). Chronic stress can alter systemic levels of glucocorticoids and catecholamines (15), which may change effector functions of macrophages and lymphocytes, with downstream implications for immune responses (16), reactivity to asthma triggers, airway inflammation, and airflow obstruction (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of wheeze in the 12 months prior to study in 2nd, 4th, 6th, and 8th graders was 12.4%, 9.9%, 9.3%, and 5.6%, respectively, and the prevalence of eczema, defined as an itchy flexural rash, during the same period was 20.1%, 18.0%, 14.0%, and 12.4%, respectively. The ORs of wheeze symptoms were higher in younger children, boys, those with a history of hospitalization, and those with SDQ scores in the clinical range, and were lower in children in the most recent surveys (Surveys 2013 and2014). Regarding ORs for eczema, younger age, girls, a history of hospitalization, SDQ scores in the clinical range, and coastal municipality were shown to be significant factors.…”
Section: Discussionmentioning
confidence: 83%
“…The influence of PTSD on asthma remains uncertain but many participants who had this condition saw a worsening of their asthma. Rosenberg et al showed that there is compelling evidence for a link between chronic psychosocial stress and the onset and course of asthma (11). Alterations in neuroendocrine pathways, as well as immunologic mechanisms, are likely to be involved in these effects, and specific signal transduction pathways through which stress modulates epigenetic and transcriptional activity in asthmarelevant cells have been suggested.…”
mentioning
confidence: 99%